Inclusive study of peanut shells derived activated carbon as an adsorbent for removal of lead and methylene blue from water - Heba M. Hashem; Mahmoud El-Maghrabey; Rania El-Shaheny (Scientific Reports, 2024)
Abstract Green and efficient agro-waste-based activated carbon has been prepared utilizing peanut shells for adsorptive elimination of an industrial dye, methylene blue, and lead from polluted water. The carbonaceous biomass obtained from peanut shells was chemically activated using either NaOH, ZnCl2, or steam and characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, and N2 adsorption and desorption studies. The adsorption process was optimal for methylene blue at alkaline pH, while pH 4.5 was optimal for Pb (II) adsorption. The adsorption takes place through pseudo-second-order kinetic, and the rate-governing step of the adsorption procedure are intraparticle diffusion and film diffusion. Furthermore, the thermodynamics of the adsorption process has been studied, and the obtained Gibbs free energy (ΔG°) values are negative (− 35.90 to − 43.59 kJ mol−1) indicating the spontaneous adsorption of the investigated pollutants on the prepared activated carbon. As per the correlation coefficient, the obtained results were best fit by the Langmuir isotherm with maximum adsorption capacity of 303.03 mg g−1 for methylene blue and 130.89 mg g−1 for Pb (II). The activated carbon successfully removed methylene blue and Pb (II) with %removal exceeding 95%. The mechanisms of interaction of Pb (II) with the activated carbon is a combination of electrostatic interaction and ion exchange, while methylene blue interacts with the activated carbon via π–π interaction, hydrogen bonds, and electrostatic interaction. Thus, the prepared activated carbon has been employed to decontaminate wastewater and groundwater samples. The developed agro-waste-based activated carbon is a promising, cost-efficient, green, and accessible tool for water remediation.